CONSÉQUENCES PSYCHO-SOCIALES DE LA MALADIE RÉNALE CHRONIQUE CHEZ LES HÉMODIALYSÉS DU CNHU-HKM DE COTONOU (BÉNIN) - AHOUI, SERAPHIN; Djidonou, ANSELME; VIGAN, JACQUES; AGBOTON, LÉOPOLD BRUNO; BIAO, HERMANN; AKOBI, JACQUES; HOUNYE, EDOUARD; HOUETO, NICANOR; TOGNON TCHEGNONSI, FRANCIS; GANDAHO, PROSPER (My University, 2017)
Introduction : The psycho-social consequences of chronic kidney disease (CKD) are not negligible. Objective : To study the psycho-social consequences of the CKD in hemodialysis patients at the National Teaching Hospital of Cotonou (Benin) in 2018. Method : This was a descriptive cross-sectional study carried out from July 1st to August 31st, 2018, and focused on chronic hemodialysis patients from the National Teaching Hospital of Cotonou. Included were patients on hemodialysis for more than three months, over the age of 18 years, volunteers, able to answer questions and giving their consent. Sampling was exhaustive. The psycho-social problems studied were: attitude towards the announcement of dialysis, criticism, insults, discrimination and stigmatization of hemodialysis patients ; respect for privacy and confidentiality, reception in the service, solicitation of help Results : A total of 110 patients were collected. The mean age was 47.19 ± 11.34 years [range of 22 years and 78 years]. The sex ratio was 1.9. Average seniority in hemodialysis was 6.61 ± 5.02 years. Faced with the announcement of the dialysis 36.36% had a resignation. In comparison to the aid, 74.55% sought help and 65 of them received it from their families and 82.73% could not carry out the projects in progress. Of the participants, 44.55% were rejected by those around them, 4.55% had a break-up, 31.82% felt discriminated against, 13.89% were exposed to criticism and / or insults, 4.47% stigmatized 78.18% were satisfied with respect for privacy during dialysis. Conclusion : The hemodialysis undergoes, by the socio-family and professional environment, a strong psychosocial influence.
Keywords: hemodialysis; psychosocial experience; Benin